Pseudorandom bit generator based on Edwards curve isomorphic transformations - Чевардін, Владислав Євгенійович (Ukrainian Scientific Journal of Information Security, 2015)
This article provides an improved standardized pseudorandom bit generator on elliptic curves through the use of additional functions to get an isomorphic transformation of the base elliptic curve. Isomorphic transformation is used for each point witch obtained after the scalar multiplication of the base point in the cyclic subgroup. In this way it is possible to use the whole set of elliptic curve isomorphic transformations and increase the number of generator internal states and, as a consequence, increase the resistance to recovery of pseudorandom sequence. The elliptic curve is used in the Edwards form, which reduces the computational cost in the generation of the pseudorandom sequence. The results of the analyses of the statistical security are confirmed its security. An improved pseudorandom bit generator can reduce the computational complexity of the algorithm and increase its capacity compared with a standardized algorithm.